Effect of Leadership Style and Organizational Climate on Work Motivation - Khan, Feroj (Digital Repository of Theses, 2025)
This study offers an in-depth examination of the intricate relationships that affect workplace dynamics by examining the linkages among employee work motivation, organizational climate, and leadership styles. The transformational and transactional styles of leadership, which are both considered to have a significant effect on how motivated employees are, are used to analyse leadership as a crucial organizational component. In order to assess their effects on work motivation, the study also explores organizational climate factors as autonomy, innovation, organizational support, and interactive cooperation. These components work together to create a comprehensive framework for understanding how motivation works in workplace settings. The results demonstrate a significant correlation between higher levels of work motivation and transformational leadership, which is defined by vision, inspiration, and personal influence. Through setting clear expectations and rewarding goal achievement, transactional leadership, which places an emphasis on organized procedures and rewards, also has a favourable effect on motivation. It has been demonstrated that the two leadership styles have different but complimentary effects on the motivating results of employees. The study emphasizes the value of encouraging innovation in corporate environment, where problem-solving and creative thinking are valued, as this substantially increases motivation. One important factor that influences employees’ motivated behaviours is organizational support, which includes giving them tools, acknowledging them, and creating a supportive environment. The study additionally examines at how organizational climate and leadership styles interact, showing how they have a positive effect on work motivation. This integrated perspective highlights the interconnection of supportive organizational environments and successful leadership as motivational factors. Businesses are better positioned to motivate staff and attain long-term success when leadership methods are in line with an environment that values creativity, support, independence, and collaboration. This study advances our knowledge of the mechanisms underpinning work motivation by combining these ideas. It offers organizations practical suggestions for raising worker satisfaction, engagement, and productivity. This study offers an insightful framework for academics and professionals alike, highlighting the need for comprehensive approaches that combine organizational climate improvement and leadership development in order to develop a driven and productive workforce. Keywords: Leadership Style, Organizational Climate, Work Motivation, Regression Analysis.